Neuronal mechanism of innate rapid processing of threating animacy cue in primates: insights from the neuronal responses to snake images - Setogawa, Tsuyoshi; Matsumoto, Jumpei; Nishijo, Hisao; Nishimaru, Hiroshi (Frontiers in Psychology, 2024)
To survive in nature, it is crucial for animals to promptly and appropriately respond to visual information, specifically to animacy cues that pose a threat. The subcortical visual pathway is thought to be implicated in the processing of visual information necessary for these responses. In primates, this pathway consists of retina-superior colliculus-pulvinar-amygdala, functioning as a visual pathway that bypasses the geniculo-striate system (retina-lateral geniculate nucleus-primary visual cortex). In this mini review, we summarize recent neurophysiological studies that have revealed neural responses to threatening animacy cues, namely snake images, in different parts of the subcortical visual pathway and closely related brain regions in primates. The results of these studies provide new insights on (1) the role of the subcortical visual pathway in innate cognitive mechanisms for predator recognition that are evolutionarily conserved, and (2) the possible role of the medial prefrontal cortex (mPFC) and anterior cingulate cortex (ACC) in the development of fear conditioning to cues that should be instinctively avoided based on signals from the subcortical visual pathway, as well as their function in excessive aversive responses to animacy cues observed in conditions such as ophidiophobia (snake phobia).